2021
DOI: 10.20961/lar.v19i2.49186
|View full text |Cite
|
Sign up to set email alerts
|

Penambahan PGF2α dalam pengencer semen dapat meningkatkan motilitas pasca thawing motility spermatozoa domba Waringin

Abstract: <p class="MDPI17abstract"><strong>Objective: </strong>The purpose of this research was to find out the rise of spermatozoa motility of Waringin sheep which was given additional amount of PGF2α in commercial semen diluents (Andromed).</p><p class="MDPI17abstract"><strong>Methods: </strong>A total of 3 Waringin sheep aged 2-3 years were used in this study. Semen samples were collected using an artificial vagina and evaluation of the quality of the spermatozoa was carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In vivo administration of PGF2α can increase the motility of frozen spermatozoa of Nubian goats after thawing [12]. In addition, an increase in the quality of spermatozoa due to the addition of PGF2α in vitro to the diluent medium has been reported in Nubian goat [15] and in Waringin sheep [13]. Therefore, it is necessary to conduct a study that compares the effectiveness of two administration methods on the same breed of goats to obtain the most effective method to improve the semen quality of Gembrong goats.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In vivo administration of PGF2α can increase the motility of frozen spermatozoa of Nubian goats after thawing [12]. In addition, an increase in the quality of spermatozoa due to the addition of PGF2α in vitro to the diluent medium has been reported in Nubian goat [15] and in Waringin sheep [13]. Therefore, it is necessary to conduct a study that compares the effectiveness of two administration methods on the same breed of goats to obtain the most effective method to improve the semen quality of Gembrong goats.…”
Section: Introductionmentioning
confidence: 97%
“…Spermatozoa quality can be improved in various ways. Recent studies revealed that the addition of prostaglandin F 2 D (PGF 2 D) can enhance the quality of spermatozoa through in vivo [12][13][14] and in vitro [15] administrations because PGF 2 D can work directly or indirectly.…”
Section: Introductionmentioning
confidence: 99%